Frequency of SARS-CoV-2 Infections among Healthcare Workers in Germany: 3-Year Follow-Up Study - Christian Stammkötter; Laura Thümmler; Johannes Korth; Beate Marenbach; Peer Braß; Peter A. Horn; Monika Lindemann; Ulf Dittmer; Oliver Witzke; Hana Rohn; Adalbert Krawczyk (MDPI AG, 2024)
The emergence of SARS-CoV-2 in 2019 led to a global pandemic with a significant impact on healthcare systems. Healthcare workers were particularly vulnerable due to frequent contact with COVID-19 patients. Despite vaccination, they remained at higher risk as the vaccines provided limited protection against infection with viral variants, like Delta or Omicron BA.1 and BA.5. Three years after the onset of the pandemic, we evaluated SARS-CoV-2 infection frequencies among healthcare workers with varying levels of patient contact: high-risk (frequent COVID-19 patient contact), intermediate-risk (non-COVID-19 patient contact), and low-risk (no patient contact). We assessed their cellular and humoral immune responses based on their vaccination status and number of prior infections. SARS-CoV-2-specific antibodies were measured by immunoglobulin ELISA, and neutralizing antibody titers were determined against the viral variants D614G, Delta, and Omicron BA.1 and BA.5. Cellular immune responses were analyzed using an interferon-γ ELISpot. Notably, three years into the pandemic, healthcare workers in daily contact with COVID-19 patients did not have higher infection rates compared to healthcare workers with non-COVID-19 patient contact or no patient contact. Immune responses were similar across all groups, highlighting the effectiveness of vaccination and current hygiene standards in preventing virus transmission from patients to staff.